LUMION. More time to design, less time to wait for renders - Kussebayev U.K. Кусебаев У.К.; Askarbekova A. Аскарбекова А.Е. (Рroblems of engineering and professional education, 2023)
: Lumion is a software solution for architects, urban planners and designers with a set of powerful tools for real-time 3D visualization. Ideal for creating videos, static renderings and creating a vibrant, dynamic presentation. It is compatible with other 3D graphics packages (Sketchup, 3ds Max, etc.), which plays an important role in the complex creation of the project.